KAJIAN PENGGUNAAN LAPORAN KEUANGAN BERBAGAI PERUSAHAAN DI SURAKARTA - TRIO HANDOKO (MANAJEMEN DAN KEUANGAN, 2007)
Research goal is to know management consistancy to using basic accrual for making financial statement and to understand resistantions in case basic accrual is useless. And as an independent variable are Employee skill, size of company, and degree of understanding about financial report and basic accrual, and consistancy to use basic accrual is a dependent variable. Surakarta is research area with 30 respondens from manufacture and trading company. This research using multiple tinier regretion analisys to know consistancy level to use basic accrual on order making financial report at manufacture and trading company in Surakarta. Beside multiple linier regretion, this research also use t test, F test and determination coefficient and also multiple corelation to show degree of relationship between influence variables and influenced variables. From data analisys has know that consistancy level to use basic accrual in arranging financial statement manufacture and trading company in Surakarta is 54%. This means, manufacture and trading company in Surakarta is understands enought about basic accrual and has been applied as a basic in making financial report.